Exploring Responses to the Collapse of Devolution in Northern Ireland 2017–2020 through the Lens of Multi-Level Governance. Issue 3 (19th March 2021) - Heenan, Deirdre; Birrell, Derek
Abstract: The system of devolution set up in Northern Ireland in 1999 has proved volatile and unstable. In 2017, the Northern Ireland Executive collapsed, following the resignation of the Sinn Féin, deputy First Minister. For a three-year period, Executive and legislative devolution ceased to operate. The UK Government opted not to impose Direct Rule from Westminster, as happened previously. This article examines the consequences of the absence of a devolved government in the context of the existing system of multi-level governance (MLG). It is contended that mitigating action taken or considered to address the gap in governance can be best understood using an analytical framework drawn from the lens of MLG. A range of interventions, adjustments and interactions occurred involving the remaining levels of MLG. Despite the fall of the Executive and Assembly an amended form of governance continued to function in Northern Ireland.